Phytochemical-based nanodrugs going beyond the state-of-the-art in cancer management—Targeting cancer stem cells in the framework of predictive, preventive, personalized medicine - Koklesova, Lenka; Jakubikova, Jana; Cholujova, Dana; Samec, Marek; Mazurakova, Alena; Šudomová, Miroslava; Pec, Martin; Hassan, Sherif T. S.; Biringer, Kamil; Büsselberg, Dietrich; Hurtova, Tatiana; Golubnitschaja, Olga; et al. (Frontiers in Pharmacology, 2023)
Cancer causes many deaths worldwide each year, especially due to tumor heterogeneity leading to disease progression and treatment failure. Targeted treatment of heterogeneous population of cells - cancer stem cells is still an issue in protecting affected individuals against associated multidrug resistance and disease progression. Nanotherapeutic agents have the potential to go beyond state-of-the-art approaches in overall cancer management. Specially assembled nanoparticles act as carriers for targeted drug delivery. Several nanodrugs have already been approved by the US Food and Drug Administration (FDA) for treating different cancer types. Phytochemicals isolated from plants demonstrate considerable potential for nanomedical applications in oncology thanks to their antioxidant, anti-inflammatory, anti-proliferative, and other health benefits. Phytochemical-based NPs can enhance anticancer therapeutic effects, improve cellular uptake of therapeutic agents, and mitigate the side effects of toxic anticancer treatments. Per evidence, phytochemical-based NPs can specifically target CSCs decreasing risks of tumor relapse and metastatic disease manifestation. Therefore, this review focuses on current outlook of phytochemical-based NPs and their potential targeting CSCs in cancer research studies and their consideration in the framework of predictive, preventive, and personalized medicine (3PM).